2021
DOI: 10.1136/jitc-2021-003468
|View full text |Cite
|
Sign up to set email alerts
|

Bispecific antibody targeting TROP2xCD3 suppresses tumor growth of triple negative breast cancer

Abstract: BackgroundTriple negative breast cancer (TNBC) is a subtype of breast cancers with poor prognosis and targeted drug therapies are limited. To develop novel and efficacious therapies for TNBC, we developed a bispecific antibody F7AK3 that recognizes both trophoblast cell surface antigen 2 (TROP2) and CD3 and evaluated its antitumor activities both in vitro and in vivo.MethodsThe binding affinities of F7AK3 to the two targets, TROP2 and CD3, were evaluated by surface plasmon resonance. Binding of F7AK3 to TNBC c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Such characteristics have rendered TROP2 an attractive target antigen for various types of cancer immunotherapy, especially in TNBC (229). In this regard, a recent study by Liu et al has reported that TRBAs targeting TROP2 and CD3 suppress tumor growth in both TNBC cell lines and primary tumor cells (231). In detail, the TROP2-CD3 TRBAs developed by these researchers were capable of recruiting T lymphocytes to TROP2-positive tumor cells in vitro and into tumor tissues in xenograft TNBC preclinical models (231).…”
Section: Trophoblast Cell-surface Antigen 2 (Trop2)mentioning
confidence: 99%
See 1 more Smart Citation
“…Such characteristics have rendered TROP2 an attractive target antigen for various types of cancer immunotherapy, especially in TNBC (229). In this regard, a recent study by Liu et al has reported that TRBAs targeting TROP2 and CD3 suppress tumor growth in both TNBC cell lines and primary tumor cells (231). In detail, the TROP2-CD3 TRBAs developed by these researchers were capable of recruiting T lymphocytes to TROP2-positive tumor cells in vitro and into tumor tissues in xenograft TNBC preclinical models (231).…”
Section: Trophoblast Cell-surface Antigen 2 (Trop2)mentioning
confidence: 99%
“…In this regard, a recent study by Liu et al has reported that TRBAs targeting TROP2 and CD3 suppress tumor growth in both TNBC cell lines and primary tumor cells (231). In detail, the TROP2-CD3 TRBAs developed by these researchers were capable of recruiting T lymphocytes to TROP2-positive tumor cells in vitro and into tumor tissues in xenograft TNBC preclinical models (231). The data presented by this study supports the potential of TROP2 for the immunotherapy of TNBC in patients with advanced/metastatic neoplasms (231).…”
Section: Trophoblast Cell-surface Antigen 2 (Trop2)mentioning
confidence: 99%
“…Furthermore, inorganic nanovehicles aid precise targeted delivery of CRISPR/Cas cargo for in vivo therapy. The next-generation single-chain antibodies [ 23 , 233 ], antigen-binding fragments [ 23 ], aptamers (single-stranded oligonucleotides) [ 235 ], AS1411 (G rich DNA oligonucleotide) [ 324 ], and peptides [ 55 ] can be easefully conjugated on the polymer-coated surface of nanovehicles, which will promote targeting in TNBC. After successful internalization of CRISPR-nano complex via endocytosis, the complex face acidic environment and multiple catalytic enzymes of endosome that can inactive CRISPR/Cas components.…”
Section: Design Strategies For Effective Crispr-nano Engineering In Tnbcmentioning
confidence: 99%
“…Thus, much research has been dedicated to the comprehension of the fundamental mechanisms leading to inducing tolerance or resistance. Currently, surplus therapies have been established to preclude acquired resistance, such as antibody-directed treatments [ 23 ], CAR-T cell-based advance immunotherapy [ 24 ] and targeted therapy or gene therapy like CRISPR/Cas system [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Novel gene vectors within a population have also been shown to provide information on proliferative capacity, migration tendency, stemness capability, and treatment targets ( Jiang et al, 2021 ; Xu et al, 2021 ). Further investigations into breast cancer have previously yielded fundamental marker discoveries including Mki67 + as a prognostic marker, Cd44 + / Cd24 + as a breast cancer stem cell marker, and Trop2 as another therapeutic target ( Ricardo et al, 2011 ; Xiong et al, 2019 ; Liu et al, 2021 ). Gene vectors also assist cell type deconvolution and functional prediction with markers such as epithelial cell adhesion molecule ( Epcam ), actin alpha 2 ( Acta2 ), and collagen type 1 alpha two chain ( Col1a2 ) expressed significantly in luminal, myoepithelial, and fibroblast cell types, respectively ( Prater et al, 2014 ; Visvader and Stingl, 2014 ; Muhl et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%